2010
DOI: 10.1007/s00214-010-0750-6
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion-corrected energy barriers for silylene addition to white phosphorus, a density functional investigation into substituent effects

Abstract: A density functional investigation into differently substituted silylenes with respect to the first step in the addition to white phosphorus is presented. The investigations include dispersion corrections in the density functional treatment. They become sizable for the transition state geometries for the silylenes as they become increasingly substituted by bulky groups. Hence, dispersion corrections are essential for a quantum chemical treatment of real molecules using density functional theory. The different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…DFT calculations by Schoeller et al for the truncated compound Me NacNac′Si ( Me NacNac′ [MeNC(CH 2 )-CHC(Me)NMe] 2− ) suggested that unlike the typical reactions of P 4 with nucleophiles (e.g., alkoxides), this reaction should be described as an electrophilic attack of silylene at a P−P edge of the phosphorus tetrahedron. 280,281 The alternative nucleophilic attack at a phosphorus corner was discarded because the silicon lone pair was regarded to be inert while the direct insertion of Me NacNac′Si into the P−P bond was found to be a high energy process. Counterintuitively, electrophilic P−P bond cleavage is facilitated by about 4 kcal mol −1 through coordination of another molecule of P 4 which acts as an external nucleophile toward the silylene, such that in the transition state the silicon atom adopted a distorted trigonal bipyramidal geometry.…”
Section: E−e Bond Activationmentioning
confidence: 99%
“…DFT calculations by Schoeller et al for the truncated compound Me NacNac′Si ( Me NacNac′ [MeNC(CH 2 )-CHC(Me)NMe] 2− ) suggested that unlike the typical reactions of P 4 with nucleophiles (e.g., alkoxides), this reaction should be described as an electrophilic attack of silylene at a P−P edge of the phosphorus tetrahedron. 280,281 The alternative nucleophilic attack at a phosphorus corner was discarded because the silicon lone pair was regarded to be inert while the direct insertion of Me NacNac′Si into the P−P bond was found to be a high energy process. Counterintuitively, electrophilic P−P bond cleavage is facilitated by about 4 kcal mol −1 through coordination of another molecule of P 4 which acts as an external nucleophile toward the silylene, such that in the transition state the silicon atom adopted a distorted trigonal bipyramidal geometry.…”
Section: E−e Bond Activationmentioning
confidence: 99%
“…For the reaction of 1 with white phosphorus, it is mandatory to briefly consider the molecular orbital system of P 4 . Symmetry considerations , give support to the following qualitative model (Scheme ).…”
Section: Resultsmentioning
confidence: 74%
“…The latter is then ready for facile subsequent rearrangements, ending finally in an energetic sink 3 . Consequently, 1 acts overall differently than substantiated previously , for carbenes and silylenes.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation